Brazilian Women's Health after 65 Years of Age - Fonseca, Angela Maggio da; Bagnoli, Vicente Renato; Massabki, Josefina Odete Polak; Arie, Wilson Maça Yuki; Azevedo, Raymundo Soares; Soares Jr, José Maria; Baracat, Edmund C. (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Purpose The aim of this study was to evaluate the health aspects of Brazilian women older than 65 years of age.Design This was a retrospective study that included 1,001 Brazilian women cared for in the gynecological geriatric outpatient office of our institution. We report a cross-sectional analysis of female adults aged over 65 years, including data on demographics, clinical symptoms such as vasomotor symptoms, associated morbidities, physical examination and sexual intercourse. We used the chi-squared test to assess the data.Results The age of the patients on their first clinic visit ranged from 65 to 98 years, with a mean age of 68.56 ± 4.47 years; their mean age at the time of natural menopause was 48.76 ± 5.07 years. The most frequent clinical symptoms reported during the analyzed period were hot flashes (n = 188), followed by arthropathy, asthenia, and dry vagina. The most frequent associated morbidities after 65 years of age were systemic arterial hypertension, gastrointestinal disturbance, diabetes mellitus, and depression, among others. The assessment of the body mass index (BMI) found decreases in BMI with increased age. At the time of the visit, 78 patients reported sexual intercourse. The majority of women reporting sexual intercourse (89.75%, n =  70) were between 65 and 69 years of age, 8.97% (n = 7) were between 70 and 74 years of age, and only 1.28% (n = 1) of those were aged older than 75 years.Conclusions Our findings suggested that vasomotor symptoms can persist after 65 years of age. There was a significant decrease in sexual intercourse with increased age. The cardiovascular disturbances in our study are health concerns in these women.
Keywords: aging; menopause; vasomotor symptoms; body mass index; sexual intercourse